New record of planktonic diatoms from the Sundarban Mangrove Forests, Bangladesh - Aziz, Abdul (Bangladesh Journal of Botany, 2012)
Botanical expedition to the Sundarban Mangrove Forests in the Bangladesh part revealed the presence of 14 diatom taxa not recorded so far from Bangladesh territory. The taxa are Amphiprora alata Kütz., Chaetoceros pendulus Karsten, Chaetoceros socialis Lauder, Cyclotella comta (Ehr.) Kütz. Thalassionema nitzschioides (Grun.) Meresch, Thalassiosira rotula Meunier, Thalassiosira weisflogii Grun., Lioloma delicatula (Cupp) Hasle, Navicula brekkaensis Petersen fa, Nitzschia inconspicua Grun. fa, Nitzschia romana Grun., Surirella fastuosa var. recedens (Schm.) Cl. Besides these, unidentified species of Chaetoceros sp. and an unidentified centric diatom have been recorded. These newly recorded taxa are described and illustrated. Key words: Phytoplankton; Diatoms; Mangrove; Estuarine algae; Centrales; Pennales DOI: http://dx.doi.org/10.3329/bjb.v40i2.9772 Bangladesh J. Bot. 40(2): 163-169, 2011 (December)